COMPLEX APPRAISAL OF WORKING CONDITIONS OF WORKERS IN SHOPS OF CHILL CASTING - A. M. Lazarenkov; S. A. Horeva; V. A. Kalinichenko (Литьë и металлургия)
Complex appraisal of  working conditions of  workers in shops of  chill casting is given. Classification of  working places by working conditions in shops of  chill casting is given.